Komparasi Hukum Pidana Korupsi: Studi Perbandingan Hukum Pidana Korupsi di Indonesia dan Singapura - Safitri, Aisha Mutiara; Kusumawati, Andriana; Pamungkas, Oki Giri (PT Elaborium Elevasi Indonesia, 2023)
Corruption is a serious threat to social, economic, and political development, especially in Asia, including Indonesia and Singapore. Singapore has succeeded in enforcing an efficient and focused criminal law approach to tackling corruption, while Indonesia faces challenges in optimizing its legal framework. Differences in definitions of criminal acts of corruption, types of criminal acts regulated, and approaches to law enforcement highlight the importance of considering the cultural context and legal system in strategies for dealing with corruption. In analyzing legal issues related to criminal regulation in Indonesia and Singapore, journal writing uses a legal comparative method approach. The main data collection was carried out through the analysis of legal documents, such as laws, government regulations, court decisions, and other regulations related to criminal law on corruption in both countries. Data is also obtained through legal literature, journal articles, research reports, and other official sources of information. Comparative analysis confirms that efficiency, transparency, and institutional collaboration are the keys to success in eradicating corruption. Writing this journal provides valuable insight into facing the challenges of corruption and strengthening law enforcement as a step towards justice and integrity in the justice system. The results of this analysis have the potential to provide important insights into global efforts to address rampant corruption practices.